2018
DOI: 10.1016/j.diff.2018.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Development of the human bladder and ureterovesical junction

Abstract: The urinary bladder collects urine from the kidneys and stores it until the appropriate moment for voiding. The trigone and ureterovesical junctions are key to bladder function, by allowing one-way passage of urine into the bladder without obstruction. Embryological development of these structures has been studied in multiple animal models as well as humans. In this report we review the existing literature on bladder development and cellular signalling with particular focus on bladder development in humans. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0
10

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 62 publications
0
33
0
10
Order By: Relevance
“…The cranial end of the ureteric bud becomes the renal pelvis and the stalk of the bud becomes the ureter. The common nephric duct (the most posterior part of the mesonephric duct) then undergoes apoptosis which brings the ureters into contact with the urogenital sinus epithelium and, after extensive epithelial remodelling, to their final trigonal positions [24,25] (Figures 4 and 5).…”
Section: Embryologymentioning
confidence: 99%
“…The cranial end of the ureteric bud becomes the renal pelvis and the stalk of the bud becomes the ureter. The common nephric duct (the most posterior part of the mesonephric duct) then undergoes apoptosis which brings the ureters into contact with the urogenital sinus epithelium and, after extensive epithelial remodelling, to their final trigonal positions [24,25] (Figures 4 and 5).…”
Section: Embryologymentioning
confidence: 99%
“…1). The urethra begins at the bladder neck (Cunha et al, 2018b; Liaw et al, 2018), which was rarely identified in these gross pelvic specimens. The prostate (rarely seen in these gross specimens) is located below the bladder and encloses the prostatic urethra (Cunha et al, 2018b).…”
Section: Resultsmentioning
confidence: 99%
“…The bladder arises from the urogenital sinus which is endodermal in origin (Liaw et al, 2018). The urethra of the human male and female extends caudally through the pelvis and is continuous with the urethral (and vestibular) plate within the developing genital tubercle.…”
Section: Introductionmentioning
confidence: 99%
“…The Q3 prostate of all species develops from the urogenital sinus (UGS), a derivative of the ventral division of the cloaca (Liaw et al, 2018;Yamada et al, 2003). Solid prostatic buds emerge from human urogenital sinus epithelium (UGE) immediately below the developing bladder at about 10 weeks of gestation (Cunha et al, 2018).…”
Section: Introductionmentioning
confidence: 99%